Magnetic damping in turning of stainless steel aisi 304 for the reduction of machining vibration and tool wear - Amin, A. K. M. Nurul; Arif, Muammer Din; Subir, Siti Aminatuzzuhriyah B. Haji; Abdullah, Fawaz Mohsen (Trans Tech Publications Ltd., Switzerland, 2015)
Chatter is a type of intensive self-excited vibration commonly encountered in machining. It reduces productivity and precision, and is more noticeable in the machining of difficult-to-cut alloys like hardened steel. In such cases chatter causes excessive tool wear, especially flank wear, which in turn affects the stability of the cutting edge leading to premature tool failure, poor surface finish, and unsatisfactory machining performance. Nowadays, however, the demand is for fine finish, high accuracy, and low operation costs. Therefore, any technique which significantly reduces chatter is profitable for the industry. This paper demonstrates the viability and effectiveness of a novel chatter control strategy in the turning of (AISI 304) stainless steel by using permanent bar magnets. Reduction in chatter and corresponding tool flank wear are compared from results for both undamped and magnetically damped turning using coated carbide inserts. Special fixtures and keyway were made from mild steel in order to affix the magnets on the lathe’s carriage. The two ferrite magnets (1500 Gauss each) were placed below and beside the tool shank for damping from Z and X directions, respectively. Response surface methodology (RSM) was used to design the experimental runs in terms of the three primary cutting parameters: cutting speed, feed, and depth of cut. A Kistler 50g accelerometer measured the vibrations. The data was subsequently processed using DasyLab (version 6) software. The tool wear was measured using scanning electron microscope (SEM). Results indicate that this damping setup can reduce vibration amplitude by 47.36% and tool wear by 63.85%, on average. Thus, this technique is a simple and economical way of lowering vibration and tool wear in the turning of stainless steel.